2010
DOI: 10.1111/j.1600-0501.2010.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival after sinus elevation with Straumann® BoneCeramic in clinical practice: ad-interim results of a prospective study at a 15-month follow-up

Abstract: This ad-interim analysis suggests that the elevation of the sinus floor with Straumann(®) BoneCeramic may be an effective clinical option over >1-year follow-up. A longer term follow-up will allow a deeper characterization of these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…Demonstrable resorption of inserted bone substitute raises the question of the long-term stability of the graft and the inserted implants, a question that has yet to be addressed by a clinical study. An interim report from a 5-year follow-up investigation suggested that augmentation of the maxillary sinus with BoneCeramic© can be an effective clinical option, with an implant survival rate of 92.5% after a mean follow-up of 14.9 ± 3.1 months (Covani et al 2011). The final results of that study will expose the clinical relevance of BoneCeramic© properties on the long-term stability of dental implants.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Demonstrable resorption of inserted bone substitute raises the question of the long-term stability of the graft and the inserted implants, a question that has yet to be addressed by a clinical study. An interim report from a 5-year follow-up investigation suggested that augmentation of the maxillary sinus with BoneCeramic© can be an effective clinical option, with an implant survival rate of 92.5% after a mean follow-up of 14.9 ± 3.1 months (Covani et al 2011). The final results of that study will expose the clinical relevance of BoneCeramic© properties on the long-term stability of dental implants.…”
Section: Discussionmentioning
confidence: 86%
“…An interim report from a 5‐year follow‐up investigation suggested that augmentation of the maxillary sinus with BoneCeramic© can be an effective clinical option, with an implant survival rate of 92.5% after a mean follow‐up of 14.9 ± 3.1 months (Covani et al. ). The final results of that study will expose the clinical relevance of BoneCeramic© properties on the long‐term stability of dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic calcium phosphate granules are 1-2 mm in diameter and have been used as bone substitutes for sinus augmentation and other dental applications for many years (Piattelli et al 1996). Recently, some studies have demonstrated the effectiveness of HA/TCP in sinus augmentation (Daculsi et al 2003;Artzi et al 2008;Cordaro et al 2008;Froum et al 2008;Lee et al 2008;Ripamonti et al 2008;Friedmann et al 2009;Frenken et al 2010;Covani et al 2011).…”
mentioning
confidence: 99%
“…Apparently, there is only a little information on the time‐dependent three‐dimensional stability of various bone graft materials and composites used for MSA. Biphasic calcium phosphate (BCP) was successfully used for MSA and its clinical suitability has been proved in several clinical studies . It consists of hydroxyapatite (HA) and β‐tricalcium phosphate (TCP) in a 60:40 ratio, thus representing a composition of both nonresorbable and resorbable nature.…”
Section: Introductionmentioning
confidence: 99%
“…Biphasic calcium phosphate (BCP) was successfully used for MSA and its clinical suitability has been proved in several clinical studies. [12][13][14][15][16][17] It consists of hydroxyapatite (HA) and b-tricalcium phosphate (TCP) in a 60:40 ratio, thus representing a composition of both nonresorbable and resorbable nature. It was recently shown that adding BCP to autogenous bone results in a comparable volume of newly formed bone when compared to autogenous bone alone.…”
Section: Introductionmentioning
confidence: 99%